CORRELATION OF HBA1C WITH NEUTROPHIL-LYMPHOCYTE RATIO AND MONOCYTE-LYMPHOCYTE RATIO AS MARKERS OF INFLAMMATION IN TYPE 2 DIABETES MELLITUS PATIENTS AT SANJIWANI HOSPITAL FROM 2021 TO 2023 - Barsua, Ni Made Ersi Dwitami; Wiryanthini, Ida Ayu Dewi; Sutadarma, I Wayan Gede; Tianing, Ni Wayan (E-Jurnal Medika Udayana; Vol 14 No 4 (2025): E-Jurnal Medika Udayana, 2025)
ABSTRACT Chronic inflammation in type 2 diabetes mellitus (T2DM) is the main link between hyperglycemia and immune system dysfunction. Chronic inflammation that cannot be controlled can increase the risk of complications. This inflammatory state is caused by growing glycemic levels as assessed by HbA1c examination. Previous studies have shown that the neutrophil-lymphocyte ratio (NLR) and monocyte-lymphocyte ratio (MLR) are inflammatory markers that can indicate immune system dysfunction. This study aims to determine the correlation of HbA1c with NLR and MLR as markers of inflammation in T2DM patients at Sanjiwani Regional Hospital for the 2021–2023 period. This research utilized a cross-sectional method. The study sample size was 73 T2DM patients who met the research criteria. The correlation of HbA1c with NLR and MLR was analyzed using the Spearman correlation test. Of the 73 research samples, it was found that 43 people (58.9%) were men, and 30 people (41.1%) were women, with an average ± SD age of 57.88 ± 9.98 years. The median HbA1c value was 8.80% (6.5%–14.5%), the median NLR value was 2.64 (0.89–6.78), and the median MLR value was 0.22 (0.02–0.57). The results of Spearman's correlation analysis between HbA1c and NLR showed no significant correlation (r = 0.195, p = 0.098), and the correlation between HbA1c and MLR was also not significant (r = 0.146, p = 0.217). So, it can be concluded that there is no significant correlation between HbA1c with NLR and MLR. Keywords: type 2 diabetes mellitus, chronic inflammation, HbA1c, neutrophil-to-lymphocyte ratio, monocyte-to-lymphocyte ratio